Efektivitas Penyerbukan Lebah Madu Apis cerana Fabr. di Taman Hutan Raya Ir. H. Djuanda, Jawa Barat - Nuriyah, Syayidah (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
Apis cerana honey bees have visitation activities on various vegetation. The presence of bee visits has the potential for pollination or pollination which can increase the chances of fertilization for successful generative reproduction. This pollination can support increased fruit and seed production which can indirectly help preserve and increase the productivity of vegetation on agricultural and non-agricultural land such as in forests. The Ir. H. Djuanda Grand Forest Park is a conservation forest area that is widely cultivated by A. cerana honey bees by the community. So it is necessary to know the role of A. cerana in carrying out pollination success in the Ir. H. Djuanda Grand Forest Park. The purpose of this study was to determine the visitation time of A. cerana and pollination efficiency of A. cerana in Ir. H. Djuanda Botanical Forest Park. The method used was an observation study by calculating the pollination efficiency of bees, butterflies and controls on bee forage plants Calliandra calothrysus (red calliandra). Observation of pollination efficiency was carried out for 60 days by observing the formation of fruit sets or fruit ovules from 20 red calliandra flowers. The results showed that A. cerana actively visited calliandra at 06.00 - 10.00 am, then there was a significant decrease at 11.00 - 21.00 pm with an average visit of 33.33 ± 32.18 individuals per day. Apis cerana gave 75% pollination success (88 fruit set of calliandra with an average of 4.40±3.39a fruit set), significantly different from the control (50%, 37 fruit set of calliandra with an average of 1.85±2.56b fruit set) but not significantly different from the butterfly (65%, 65 fruit set of calliandra with an average of 3.25±3.01ab fruit set). So it can be concluded that A. cerana bees have a role in increasing the success of pollination of bee forage plants in the Ir. H. Djuanda Grand Forest Park.